Challenges, Benefits, and Motivations in Paraphrasing: Insights from Marine and Fisheries EFL Students - Ikhwan Wahidin; Muhammad Syauqi (PT. Global Research Collaboration, 2024)
This study explores the challenges, motivations, and benefits of paraphrasing for Marine and Fisheries EFL students, aiming to uncover factors that impact their ability to rephrase academic texts. Using a descriptive qualitative approach, data were collected through field notes and semi-structured interviews with 15 purposively sampled students. The findings reveal that students face significant challenges in paraphrasing due to limited vocabulary, difficulties in sentence restructuring, and low self-confidence. Some students perceive English proficiency as less relevant to their future careers, reducing motivation to enhance their language skills. However, regular paraphrasing practice was found to provide valuable benefits, including vocabulary expansion, improved understanding of sentence structures, and increased confidence in handling technical content. These outcomes underscore the potential of paraphrasing exercises to support academic skill-building and professional readiness in specialized fields. The study suggests the need for targeted pedagogical strategies that emphasize vocabulary development, structural flexibility, and confidence-building. These findings contribute to the understanding of paraphrasing in EFL contexts and offer practical recommendations for enhancing students’ language skills in discipline-specific academic environments.